Refracture of a malunited clavicle: angular deformity as an under-recognized biomechanical risk factor - Panchal, Lalit; Bagwe, Sagar; Rathod, Bhushan; Ambhore, Akash (International Journal of Research in Orthopaedics, 2026)
Angular deformity in clavicle fractures is often considered acceptable in adults when displacement and significant shortening are absent. However, altered biomechanics resulting from angular malunion may predispose to refracture. We report a 40-year-old male with a previously malunited clavicle fracture treated non-operatively who sustained a refracture following minor trauma. After failure of conservative management, open reduction and internal fixation with a clavicular reconstruction plate was performed. This case highlights angular malunion as an under-recognized biomechanical risk factor for clavicle refracture in adults and suggests that angular deformity should be considered during initial fracture assessment.